(untitled) (Revista Sistemas de Producción Agroecológicos, 2013)
The indiscriminate misuse of antibiotics in recent decades, for prophylaxis of diseases in man and animals, has triggered an alarm in the world of medicine microbiological, since these microorganisms have responded in a dangerous way, with called bacterial resistance, so it is necessary to recognize, investigate and apply in our professional field, there are alternative options in veterinary medicine. The objectives in the present study are to establish if the honey bee Apis mellifera (honeybee) and honey bee Tetragonisca angustula (angelita or virgin bee) obtained from our regional flora, possess some antibacterial feature inhibit microbial growth achieved in different bacterial concentrations planting, later analyze and compare them statistically. The results obtained were asked comparative and descriptive analysis of the population mean, using this program estad.graphad.instat Software version 3.06 (2003). It looked for statistically significant differences between pairs P<0.005 using multiple range test or Tukey-Kramer test. Pure honeys both Apis mellifera and the Tetragonisca angustula showed the highest inhibition in vitro bacterial concentrations 1x10-4 UFC. The diluted honey of Apis mellifera and Tetragonisca angustula 20% did not present sufficient inhibition at concentrations of 1x10-1, 1x10-2 and 1x10-3 UFC. The remaining dilutions showed no marked difference from each other by what is generally considered to four inhibitory concentrations. All honeys were within a range of 21.2 mm and maximum diameter of 11 mm as minimum, maximum obtained corresponded to pure honey bee Apis mellifera to the concentration of 1x10-4 CFU and the minimum corresponded to honey the Tetragonisca angustula in dilution to 20% at the concentration of 1x10-1 bacterial CFU. In all states honey was superior to the positive control: oxytetracycline 10%. In conclusion it was found during this study that the honey bee Apis mellifera and Tetragonisca angustula, pure and diluted to 50 and 20%, possess antibacterial properties that make them effective in stopping the growth of colonies of coagulase-positive Staphylococcus aureus, in an in vitro assay and minimum inhibitory concentrations of honey depend on bacterial concentration and pure or dilute them honeys. It could recommend that future studies of this nature are required before the presence and quantity of the catalase and glucosidase enzymes in honey under study, besides obtaining the specific moisture for it.